2020
DOI: 10.1111/jvh.13404
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and clinical characteristics of 70 cases of coronavirus disease and concomitant hepatitis B virus infection: A multicentre descriptive study

Abstract: The interaction between existing chronic liver diseases caused by hepatitis B virus (HBV) infection and COVID‐19 has not been studied. We analysed 70 COVID‐19 cases combined with HBV infection (CHI) to determine the epidemiological, clinical characteristics, treatment and outcome. We investigated clinical presentation, imaging and laboratory parameters of COVID‐19 patients of seven hospitals from Jan 20 to March 20, 2020. Multivariate analysis was used to analyse risk factors for progression of patients with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 31 publications
1
45
1
Order By: Relevance
“…There are citations of unique co-infections of SARS-CoV-2 with other systemic viral illnesses [101][102][103][104][105][106][107][108][109][110][111]. Such coinfection was particularly of interest in the context of chronic HIV infection where persistent immunocompromise or enhanced infection susceptibility otherwise might allow for either of the infections to be more severe than not [104][105][106]112].…”
Section: Co-detection Of Sars-cov-2 With Selected Non-viral Infections and Chronic Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are citations of unique co-infections of SARS-CoV-2 with other systemic viral illnesses [101][102][103][104][105][106][107][108][109][110][111]. Such coinfection was particularly of interest in the context of chronic HIV infection where persistent immunocompromise or enhanced infection susceptibility otherwise might allow for either of the infections to be more severe than not [104][105][106]112].…”
Section: Co-detection Of Sars-cov-2 With Selected Non-viral Infections and Chronic Viral Infectionsmentioning
confidence: 99%
“…These studies do not, however, indicate that either of the latter infections markedly affects the other. For chronic hepatitis B patients, early reports suggest that COVID-19 increases the potential for complicating outcomes [107,108]. Others have suggested that chronic hepatitis B did not predispose patients to a more severe outcome [109].…”
Section: Co-detection Of Sars-cov-2 With Selected Non-viral Infections and Chronic Viral Infectionsmentioning
confidence: 99%
“…An initial search in PubMed, the Cochrane Library, and Embase identified 166 citations. Six full-text articles met selection criteria and were included in the meta-analysis (8)(9)(10)(11)(12)(13).…”
Section: Selection Of Studiesmentioning
confidence: 99%
“…Clinical studies have shown that the abnormal rate and average value of serum ALT and AST levels of SARS-CoV-2-infected patients with hepatitis B virus (HBV) are higher than those in SARS-CoV-2 patients without HBV infection, which indicates that HBV is one of the risk factors for liver injury in COVID-19 patients[ 40 ]. Compared with COVID-19 without HBV infection group, patients with dual infection had a higher proportion of severe/critically ill disease, higher levels of ALT, AST and activated partial thromboplastin[ 41 ]. Of course, there are clinical reports that the abnormalities of liver function are not uncommon on COVID-19 patients with chronic HBV infection in a case series[ 42 ].…”
Section: Etiology and Pathogenesis Of Covid-19 Combined With Liver Injurymentioning
confidence: 99%